Akkermansia muciniphila plays critical roles in host health. (2nd January 2023) - Zhao, Qixiang; Yu, Jiadong; Hao, Yan; Zhou, Hong; Hu, Yawen; Zhang, Chen; Zheng, Huaping; Wang, Xiaoyan; Zeng, Fanlian; Hu, Jing; Gu, Linna; Wang, Zhen; et al.
Abstract: Akkermansia muciniphila, an intestinal microorganism, belongs to Verrucomicrobia, one of the most abundant microorganisms in the mammalian gut. It is a mucin-degrading bacterium that can colonise intestines of mammals such as humans and mice by utilising mucin as the only nitrogen and carbon source. When A. muciniphila colonises the intestine, its metabolites interact with the intestinal barrier, affecting host health by consolidating the intestinal barrier, regulating metabolic functions of the intestinal and circulatory systems, and regulating immune functions. This review summarised the mechanisms of A. muciniphila -host interactions that are relevant to host health. We focussed on characteristics of A. muciniphila in relation to its metabolites to provide a comprehensive understanding of A. muciniphila and its effects on host health and disease processes.